Common Mode Noise Generated by Magnetic Components - Experimental Test Set-up and Measurement Results - Dürbaum, Thomas; et al. (PESC00, 2000)
Common mode currents were shown to be a major source not only of conducted but also of radiated electromagnetic interference (EMI). Measurements with a switch mode power supply in a certain applications revealed that the level of common mode currents were strongly influenced by the wiring and loads connected to the switch mode power supply outputs.
UnivIS-Import:2015-04-16:Pub.2000.tech.IE.lselek.common